Origins of the Project, Historical Landscape and Cultural Heritage. Paths, Cities and Architectures of the Ionian Side of South Calabria - Francesca Martorano (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
It is my opinion that the cultural inheritance of a land must be studied before any project or intervention in order to avoid destruction or alteration resulting from ignorance of the history of a landscape. Therefore, a weak area with a very significant cultural and environmental heritage of the Ionian side of Calabria belonging to the wide “Carafa State”, yet of historical importance, was carefully studied. In 1771 Vincenzo Maria Carafa, 8th Prince of Roccella, assigned to the regio ingegnero Tommaso Rajola the task of drawing up the topographical papers of his feuds. The assignment was concluded quickly, in three years, and after 10 years, in 1783, the final drawings were ready. This iconographic work is of great importance because it provides significant information, not just economical and bureaucratic, about Carafa's feuds at the end of XVIII century.  The territorial entities from this work with the reality of today, as well as the former situation of a few decades from the beginning of XVI century when the presence of the Carafas was stabilized in the south of Calabria Ultra, yet with solutions of continuity, were compared. The urban policy used between XVI and the end of XVIII century was examined to ascertain pathways and proceedings for every feud to regulate territories and city centres and to sustain religious orders, with special regard for the towns of Condojanni and Sant'Ilario.